Implementation of real time lighting data for Pekan and validation data with lighting TNBR - Nurul Fazirah, Ghazali (2012)
Pekan are located at east of peninsular Malaysia which that like other tropical countries which experience very high cloud to ground (CG) density. Many members of public has lack information about lightning, therefore the website are responsible to publish the lightning real time data at this area. This thesis presents the real time lightning data for Pekan which detected by using LD-250 Boltex lightning detection hardware that connected to the computer and analyze the data using Lightning/2000 software. LD-250 is sensor that detect lightning using magnetic direction finder (MDF). Data collected by Lightning/2000 is compared with Tenaga Nasional Berhad Research Sdn.Bhd (TNBR) to avoid from forecast error before it can be publish to the website.